Isolation, characterization, and application of cellulose nanofibers derived from coconut husk fibers using chemical-ultrasonic process - Fuentes, Enrile B.; Dalida, Maria Lourdes P.; Advincula, Rigoberto C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Green technology is an important consideration in the growing field of nanotechnology. In this master thesis, two areas of green technology is addressed by: (1) utilizing coconut husk fiber, an agricultural lignocellulosic waste, as raw material in producing cellulose nanofibers (CNF) and (2) synthesizing a green product, silver nanoparticle supported on CNF (CNF-AgNP), that can help mitigate environmental pollutants. The CNF were isolated using a facile chemical-ultrasonic method and were characterized using transmission electron microscopy (TEM), atomic force microscopy (AFM), fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, and thermogravimetric analysis (TGA). Results showed that the extracted CNFs has mean diameter of 3.64 nm and has a very high aspect ratio. Furthermore, improved crystalline behavior and thermal properties were observed. Instead of using synthetic polymers, the isolated CNFs were used as support in the in-situ UV-assisted photochemical reduction of AgNP. The synthesized CNF-AgNP exhibited a distinct surface plasmon resonance band centered around 410 nm wavelength in its UV-visible absorption spectra and the presence of AgNPs was confirmed through X-ray photoelectron spectroscopy (XPS). In addition, TEM analysis showed that the synthesized AgNPs are spherical and have mean diameter of 7.7 nm. Moreover, the CNF AgNP nanocomposite showed excellent catalytic performance for the reduction of 4 nitrophenol, methyl orange, and rose bengal by NaBH4 in aqueous solution.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Coir; Cellulose fibers